Relationship Between Social Anxiety and Internet Addiction in Chinese College Students Controlling for the Effects of Physical Exercise, Demographic, and Academic Variables - Ye, Songdong; Cheng, Huiying; Zhai, Zongpeng; Liu, Hongyou (Frontiers in Psychology, 2021)
This study aims to identify the relationship between social anxiety (SA) and internet addiction (IA) in a group of Chinese college students by controlling for the effects of physical exercise (PE), demographic and academic variables. A sample of 4,677 students from five major regions of China participated in this survey. The findings revealed that: (1) SA had a direct effect on IA; (2) regular and active participation in physical exercise can relieve SA and IA effectively; (3) the level of SA and IA is strongly linked to sex; (4) the levels of SA and IA are different among students of different majors; (5) students in the middle phase of their academic career are more likely to have IA than those in the starting phase. The study is significant because few existing studies discuss the role of PE on SA and IA. Additionally, the study found that college students with more PE would have a lower level of SA and a lower probability of IA.